Personality Profile and Career Interest among Trainees of Malaysian Teacher Training Institute - Hamid, Siti Aishah (2009)
Previous researches have shown that there is a relationship between one’s personality and career interest. This study, framed by Holland’s Theory of Career Choices(1973;1978;1985), identifies the relationship between the personality and career interest of trainee teachers undergoing the Bachelor Degree of Education in a teacher training institute in Kedah. The research design in this study was correlational ex post facto.Two instruments were used in this study, that were Self-Directed Search and Colours Personality Inventory. The data collected were analysed by two statistical analysis that were descriptive statistics and inferential analysis. The descriptive analysis used were frequency, mean and percentage whereby the inferential analysis used was Pearson’s Correlation. The level of significance chosen was .05. The findings showed that there was a significant relationship between Green and Orange personality and vocational interest in Realistic and a significant relationship between Green, Gold and Orange personality and vocational interest in Investigative. There was also a significant relationship between Orange, Green and Blue personality with vocational interest in Artistic and there was a significant relationship between Orange, Blue and Gold personality and vocational interest in Social. The findings also showed there was a significant relationship between Orange, Gold, Green and Blue personality and vocational interest in Enterprising and a significant relationship between Orange, Gold and Green personality and vocational interest in Conventional. Based on the findings of this study, implications and suggestions were put forward.